Imagination in children's stories between ordinary thinking and creative thinking (Journal of the College of Basic Education, 2022)
This study deals with the topic ((Imagination in children's stories between ordinary thinking and creative thinking)); Because this element possesses a creative ability that contributes to the rise in the graphic line of the literary text directed to the child, and the research dealt with the story that is directed to the child exclusively, because it is one of the most literary genres that uses imagination, and its clear and significant impact on the development of imagination in the child, and how imagination has a great credit for creativity ; Likewise, imagination is the basis of thinking and creativity.